Travelling Saleman Problem via Ant Colony Optimization – An Application Toward Kedah Tourism - AZHAR , NUR AIN HUSNA; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2026)
Optimization of tourism is important for both the travel experience and operational effectiveness, especially in state with a lot of attractions such as Kedah, Malaysia. This study demonstrates the application of Ant Colony Optimization (ACO) to solve the Travelling Salesman Problem (TSP) for tourism in Kedah. The aim of this study was to identify the most efficient and shortest travel route for tourists to have the best experiences in visiting the top interesting places in Kedah. The ACO algorithm was used, resulting in a reduced total travel distance of 239.4 kilometres. This optimized route not only minimizes travel time and costs but also ensures a clear journey for tourists. The accurate solution is produced by compares the ACO results with manual calculations which highlighting the algorithm. Overall, this study offers valuable insights for tourism logistics which provide a useful tool for minimizing travel routes, reducing operational costs, and creating memorable trip for tourist in Kedah.